The use of voice recognition as a control interface for word processing. - Dalton JR; Peterson CQ (Occupational Therapy in Health Care, 1997)
The purpose of this case study was to compare the speed and accuracy of the subject's word processing skills using the Dragon Systems, Incorporated Dragon Dictate voice recognition system, to the speed and accuracy of the subject's current method of accessing a computer by mouthstick. The subject received fifteen hours of training and practice on the voice recognition technology. Following training the subject was able to type 13 words per minute using his current method of mouthstick access, resulting in 10 errors or 95.4% accuracy. Using voice recognition technology, the subject dictated 20 words per minute with 3 errors, resulting in 98.6% accuracy. The results of this objective clinical measurement indicate that voice recognition technology may be a viable means of word processing for individuals with severe upper extremity restrictions.